THEORETICAL AND METHODOLOGICAL BASIS OF ENVIRONMENTAL TRAINING AT HIGHER EDUCATIONAL INSTITUTIONS - Саєнко T. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2014)
The problem of environmental education today went beyond national boundaries and gained international significance. Experience of Western countries in the implementation of greening training for 25-30 years is preceding national measures, so with the transition to the principles of the Bologna process in higher education, our education system had to take all the positive elements of ecological disciplines, areas of training lecturers, teachers and general public